Overcoming the Persistence of Inequality and Poverty - FitzGerald, Valpy. author. aut Link
XXI, 301 p.
Keywords: International experts evaluate new policy directions in economic development and poverty reduction, building on the ideas of a pioneer in the new discipline of Development Studies, Frances Stewart. Combing ideas and evidence on technological change, human development and conflict prevention to address the issue of the persistence of inequality.